2016
DOI: 10.4103/1319-3767.182454
|View full text |Cite
|
Sign up to set email alerts
|

Are serum quantitative hepatitis b surface antigen levels, liver histopathology and viral loads related in chronic hepatitis b-infected patients?

Abstract: Background/Aims:Fluctuations in hepatitis B virus (HBV) DNA and alanine transaminase (ALT) levels complicate assessment of the phases of chronic hepatitis B (CHB) infection and correct identification of the inactive HBV carrier state. In this study, we aimed to examine the role of HBsAg quantification (qHBsAg) in the identification of the phases of HBV and to evaluate its association with liver histopathology.Patients and Methods:Inactive HBV carriers (IC) (n = 104) and CHB patients (n = 100) were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Some studies have investigated the correlation of serum HBsAg and HBV DNA with liver pathological grades and stages in patients with chronic HBV infection [31][32][33][34][35][36]. e results of this study were basically consistent with those studies.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have investigated the correlation of serum HBsAg and HBV DNA with liver pathological grades and stages in patients with chronic HBV infection [31][32][33][34][35][36]. e results of this study were basically consistent with those studies.…”
Section: Discussionsupporting
confidence: 89%
“…In HBeAg-positive CHB patients, a moderate positive correlation was detected between serum qHBsAg level and HBV DNA, but no correlation was found between the serum qHB-sAg level and ALT, HAI severity or the fibrosis stage. In HBeAg-negative hepatitis B infection and HBeAg-negative CHB group no correlation was reported between serum qHBsAg level, ALT, HAI, and fibrosis [15].…”
Section: Discussionmentioning
confidence: 85%
“…In our study we found that in the group of IC there is intermediate strong positive correlation between HBsQ and HBV DNA, Spearman Rank R=0.45 ( p<0.05), while in the HBeAg-negative group there is intermediate weak positive statically insignificant correlation Spearman Rank R=0.31 and p>0.05. In the study of Balkan [17] 204 patients with chronic hepatitis B were investigated, IC and patients with chronic active hepatitis B, and the correlation between HBsQ and HBV DNA, ALT level, liver fibrosis and HAI index was investigated. No correlation was found in the inactive carrier group, but intermediate positive correlation was found in the patients with chronic HBeAg positive hepatitis B [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Balkan [17] 204 patients with chronic hepatitis B were investigated, IC and patients with chronic active hepatitis B, and the correlation between HBsQ and HBV DNA, ALT level, liver fibrosis and HAI index was investigated. No correlation was found in the inactive carrier group, but intermediate positive correlation was found in the patients with chronic HBeAg positive hepatitis B [17]. Unlike the Balkan's study, our study did not investigate the correlation between quantitative HBsAg and serum HBV DNA in patients with chronic HBeAg positive hepatitis B, but we found intermediate positive correlation between the investigated parameters in patients with HBeAg-negative chronic hepatitis B, and not in the inactive carrier group.…”
Section: Discussionmentioning
confidence: 99%